Hydroelectric Power Generation System in Tanggari (PLTA Tanggari 2) - Deitje S. Pongoh; Johan. Pongoh; Jusuf Luther Mappadang; Samuel Mandagi; Teovano Ante; Dina Ardiani; Yehezkiel Sondakh; Alfaro Monopode (Ravine Publisher, 2025)
The research objective of PLTA Tanggari 2 is to understand and analyze the hydropower system from energy generation to distribution to end consumers, both households and industries. This research aims to improve the efficiency and performance of the entire electricity generation and distribution system. The research methodology used in making this journal is to collect sources or information related to the topic of discussion, namely hydroelectric power plants. The study explores the utilization of hydropower in the Tondano watershed to address electricity needs in North Sulawesi. Tanggari 2 Hydropower Plant exemplifies this by harnessing the potential and kinetic energy of water through a dam on the Tondano River. With an extensive watershed area of 4,700 hectares and Lake Tondano at its core, this system is optimized to efficiently generate electricity for the entire region. The input-output dynamics of hydropower plants are crucial, detailing how water flow drives turbines, ultimately leading to electrical output. This research underscores the potential of watershed utilization as an accessible, economical, and sustainable energy source for broader regional electrification endeavors. The implications of this research extend to enhancing understanding and analysis of water-based power generation systems, from energy production to distribution to end consumers. By improving the efficiency and performance of these systems, there is a significant potential for sustainable energy solutions that can benefit both households and industries in the broader regional context of North Sulawesi.